MAPPING OF LANDRACE PIGLETS MAINTENANCE MANAGEMENT COMPONENTS DURING LOCATION PERIOD IN TABANAN DISTRICT - Gunawan, I Nyoman Dodik; Sampurna, I Putu; Nindhia, Tjok Sari (Buletin Veteriner Udayana, 2022)
Tabanan Regency is a district that has a high number of pig farms, which is 94,537. This study aims to find out the components of maintenance management of piglets that have not been well implemented in each sub-district in Tabanan and know the sub-districts that have implemented the maintenance management component properly. The method of collecting data in this study is by using questionnaires analyzed by Biplot analysis, with 2 components of variables, good and bad. The results of this study the castration component and the parent colostrum have the least diversity (0), then variables that have the diversity of the smallest are housing, cutting teeth, additional feed, tail cutting, cleaning of piglets and the greatest diversity is rope cutting navel. The conclusion of this study is that not all components of the maintenance of landrace piglets are properly applied to farms in Tabanan Regency. It is necessary to educate the maintenance of landrace piglets on farms that have not implemented management well to help optimize the quality and production of piglets.